2012
DOI: 10.4236/jep.2012.32019
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Remediation Processes for a Low Level Pesticide Wastewater

Abstract: The aim of this study was to develop a remediation system for the treatment of a low-level pesticide wastewater that uses available onfarm organic matter as an absorption media, is capable of reducing the concentration of the pesticide to a safe level and is economically viable for implementation by farmers. The absorption capacity of chopped hay and soybean to the fungicide captan was evaluated under batch conditions and the effectiveness of the composting process in depredating captan in contaminated organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…On the other hand, pressure filters and vacuum filters require to be periodically replaced [29]. Sedimentation may require low power for operation but it is denoted with low separation efficiency (up to 66%) [30]. The present work showed that the target of low energy consumption and long-life parts could be met in the electrochemical harvesting process.…”
Section: Power Consumption and Operation Costmentioning
confidence: 85%
“…On the other hand, pressure filters and vacuum filters require to be periodically replaced [29]. Sedimentation may require low power for operation but it is denoted with low separation efficiency (up to 66%) [30]. The present work showed that the target of low energy consumption and long-life parts could be met in the electrochemical harvesting process.…”
Section: Power Consumption and Operation Costmentioning
confidence: 85%
“…Singh [113] reported a degradation efficiency of 96.03% for the endoslufin pesticide after 4 weeks, using composted soil with a moisture level of 38%. Al hattab and Ghaly [97] achieved a captan removal efficiency of 92.4% in the first four days using hay compost.…”
Section: Compostingmentioning
confidence: 99%
“…Memon et al [96] reported that thermally treated watermelon peels were capable of removing 99% of the methyl parathion pesticide. Al hattab and Ghaly [97] reported a captan removal efficiency of 99.2% and 98.5% using hay and soybean plant residues, respectively.…”
Section: Organic Absorbentsmentioning
confidence: 99%
“…These residues are removed from applicators by rinsing with water resulting in the formation of a toxic wastewater that represents a disposal problem for many farmers (Kearney et al, 1988). Currently, disposal of pesticide wastewater is carried out by several methods including (a) land cultivation, (b) dumping on land, in ditches, in lagoons and in soil pits and in extreme cases in sewers and streams near the rinsing operation, (c) use of evaporation ponds and (d) land filling (Al Hattab and Ghaly, 2012). These methods of disposal are totally unsafe, as the surface run off will reach streams, rivers and lakes and the infiltration of the wastewater into the local soil will eventually end up in ground water.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment methods currently used for pesticide containing wastewater include (a) incineration, (b) chemical treatment such as O 3 /Uv oxidation, Fenton oxidation and hydrolysis (c) physical treatment using inorganic and organic absorbents and (d) biological treatment such as phytoremediation, composting and bioaugmentation. These treatment methods either require land or are expensive and suffer from variability of effectiveness (Balestra and Misaghi, 1997;Winterlin et al, 1989;Al Hattab and Ghaly, 2012).…”
Section: Introductionmentioning
confidence: 99%